Meaning and relevance - Wilson, Deirdre; Sperber, Dan (Cambridge University Press, 2012)
"When people speak, their words never fully encode what they mean, and the context is always compatible with a variety of interpretations. How can comprehension ever be achieved? Wilson and Sperber argue that comprehension is a process of inference guided by precise xpectations of relevance. What are the relations between the linguistically encoded meanings studied in semantics and the thoughts that humans are capable of entertaining and conveying? How should we analyse literal meaning, approximations, metaphors and ironies? Is the ability to understand speakers' meanings rooted in a more general human ability to understand other minds? How do these abilities interact in evolution and in cognitive development? Meaning and Relevance sets out to answer these and other questions, enriching and updating relevance theory and exploring its implications for linguistics, philosophy, cognitive science and literary studies"-- Provided by publisher.